Similarity grouping and repetition blindness are both influenced by attention - De Haan, Bianca; Rorden, Chris (Frontiers in Human Neuroscience, 2010)
Previous studies have reported seemingly conflicting results regarding how the amount of stimulus similarity between two simultaneously presented target stimuli impacts perceptual performance. There are many reports of ‘repetition blindness’, where individuals do worse when shown two similar stimuli relative to two different stimuli. On the other hand, there are reports of ‘similarity grouping’, where participants perform better when identifying two similar objects relative to two different objects. This manuscript posits that repetition blindness and similarity grouping coexist and can be elicited in the same subjects in a single task. This not only explains the previous opposite effects of stimulus similarity on task performance, but also provides a unique opportunity to directly compare these opposite effects of stimulus similarity with respect to susceptibility to a modulating factor. Since previous studies have provided inconclusive results on whether attentional relevance can modulate the effect of stimulus similarity on task performance, the current manuscript aims to compare repetition blindness and similarity grouping with respect to their susceptibility to attentional relevance. The results of the first experiment confirmed that both repetition blindness and similarity grouping can be elicited in the same experiment, suggesting that repetition blindness and similarity grouping coexist. The results of the second experiment suggest that both repetition blindness and similarity grouping can be modulated by attentional relevance. These results support the explanation of repetition blindness as a token individuation failure. Furthermore, these results suggest that supposedly pre-attentional grouping mechanisms might not operate as independently from top-down attentional modulations as traditionally thought.